Panic disorder prevalence among patients referred for an electrocardiogram in a Nigerian teaching hospital (2013)
Background: Panic disorder is a common chronic illness that is often unrecognized, misdiagnosed, and untreated because it often presents to the physicians with symptoms that are similar to those of emergency medical conditions. One study of the prevalence of panic disorder in the general population in Nigeria has been published, but no studies have examined the prevalence of panic disorder in a sample of Nigerian patients with cardiac symptoms. This study investigated the 12-month prevalence of panic disorder among patients who were referred for an electro cardiogram in a Nigerian teaching hospital. Methods: Three hundred consecutive patients who were referred for an electrocardiogram were assessed for panic disorder using the Structured Clinical Interview for DSM-IV (SCID). Results: The prevalence of panic attacks and panic disorder were 10.0% and 7.0%, respectively. Age was associated with the presence of both panic attacks and panic disorder. Conclusions: This study suggests that panic disorder is common among patients who are referred for an electrocardiogram. It is recommended that patients whose cardiovascular or respiratory symptoms are not well explained by the diseases of such systems be evaluated for mental illness.